(untitled) (Tribhuvan University Journal of Microbiology, 2023)
Objectives: To explore the presence of fecal indicator bacteria and assess antibiotic resistance status in Bagmati river water. Methods: In a cross sectional study during a year 2020; a total of 180 water samples were collected from the Bagmati River’s upstream, midstream, and downstream sources. Maintaining reverse cold chain, the samples were transferred to the laboratory of central department of Microbiology, Tribhuvan University. Organisms were isolated on Eosin Methylene Blue (EMB) and Nutrient Agar. The organisms were further identified based on the biochemical properties and antibiotic susceptibility testing was performed following CLSI (2020) guidelines. Results: Of the 546 isolates, 209 (or 38%) were Escherichia coli. Other coliforms isolated were Enterobacter spp (2%), Citrobacter spp (37%), and Klebsiella spp (23%). Upstream source revealed least percentage 3% (7/209) of E. coli. All the recovered Citrobacter spp. were resistant and E. coli showed >99% resistance towards Tetracycline, Ampicillin and Amoxiclav antibiotics. Klebsiella spp. was 100% resistant towards Ampicillin and Amoxiclav antibiotics. The coliforms exhibited least resistance (10%) towards Chloramphenicol. Based on antibiotic resistance percentage pattern, E. coli showed 27% similarity to Citrobacter spp. Conclusion: Coliforms showed maximum resistance towards first line antibiotics prescribed in human infection. Immediate water safety plans should be instituted to improve the water quality.